+0  
 
0
52
1
avatar+979 

Find the asymptote of -4x^2 + y^2 - 2y = 3 with positive slope.

 Nov 30, 2020
 #1
avatar+114592 
+2

-4x^2  +  y^2  - 2y  =  3       re-write  as

 

y^2 - 2y   - 4x^2   = 3     complete the square on  y

 

y^2  - 2y + 1   - 4x^2  = 3  + 1

 

( y - 1)^2   - 4x^2    =  4      divide  both sides  by 4

 

(y - 1)^2            x^2

_______   -     _____   =    1

      4                  1

 

a^2 =  4        b^2  =1

a = 2              b  =1

 

The center is  (0, 1)  = (h, k)

 

Equation  of asymptote with a positive  slope   = 

 

y = ( a/b) ( x - h)  +  k

 

y= (2/1) ( x -  0)  +  1

 

y = 2x  + 1

 

See the graph here :  https://www.desmos.com/calculator/bbtkhsfpum

 

 

cool cool cool

 Nov 30, 2020

64 Online Users

avatar
avatar
avatar
avatar